Pengaruh Kemudahan Penggunaan, Keamanan Privasi, Dan Electronic Word Of Mouth Terhadap Loyalitas Pelanggan Marketplace Di Indonesia Dengan Mediasi E-Satisfaction - Wulandjani, Harimurti; Supriadi Thalib; Widarto Rachbini; Aryo Seno; Ahmad Fikri (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2025)
The rapid growth of online marketplaces in Indonesia has significantly transformed consumer shopping behavior. Increasing competition requires each platform to maintain customer satisfaction and loyalty through various factors, such as ease of use, security & privacy, and electronic word of mouth (e-WOM). This study aims to analyze the influence of these factors on customer loyalty in Indonesian marketplaces, with e-satisfaction as a mediating variable. A quantitative explanatory research approach was employed by conducting an online survey of 380 active marketplace users. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that ease of use and e-WOM have a significant positive effect on both e-satisfaction and customer loyalty. Meanwhile, security & privacy do not directly affect loyalty but significantly influence e-satisfaction. Furthermore, the findings confirm that e-satisfaction plays a strong mediating role in the relationship between independent variables and customer loyalty. The study implies that enhancing user satisfaction is a key strategy for fostering long-term customer loyalty in Indonesian marketplaces.